EVALUATION OF MECHANICAL AGITATION EFFECT ON MICROSCOPIC FILAMENTOUS FUNGI CULTURING EFFICACY - Motronenko, Valentyna; Ruzhynska, Luidmyla; Chumak, Vitalii; Galkin, Oleksandr (Proceedings of National Aviation University (archive), 2017)
Goal: Comparative evaluation of the effect of agitation modes on viability and productivity of filamentous fungi in submerged cultivation conditions using the existing literature data. Selection of culturing mode providing the maximum end product yield. Methods: Investigation of agitation modes in laboratory fermenters with mechanical agitation devices was performed in the articles reviewed. The experiments were carried out for the selected agitator type by variation of agitation device rotation frequency in the apparatus. Results: As can be seen from the evaluation performed, mechanical agitation intensity plays an important role in submerged cultivation. The average stirrer rotation rate is 120-180 rpm.